LEGAL FOUNDATIONS OF CIVIL PROCEEDINGS IN UKRAINE AND IRELAND: A COMPARATIVE ANALYSIS - Alina S. Chala; V.V. Barankova (Alfred Nobel University Journal of Law, 2025)
The article provides a comparative analysis of the civil procedural law of Ukraine and Ireland with the aim of identifying common features and differences between the two legal systems. The study examines the sources of law, the principles of justice, the organization of the judicial system, and the influence of international legal standards on national procedural legislation. Special attention is paid to such fundamental principles as adversarial proceedings, equality of parties, judicial independence, reasonable time for trial, and access to justice. In the context of the ongoing judicial reform in Ukraine and its aspirations for European integration, it is particularly relevant to explore the experience of European Union member states, especially Ireland, which combines features of the Anglo-Saxon legal tradition with the effective functioning of judicial power. The article provides a detailed analysis of the extent to which Ireland’s civil justice mechanisms can be adapted to Ukrainian realities, taking into account cultural, political, and legal characteristics. The research is based on comparative legal, formal legal, and systemic methods. The article focuses on the procedural aspects of civil cases in courts of first instance, appellate, and cassation courts. The comparison reveals several progressive elements of Ireland’s civil procedure that could contribute to increasing the efficiency of Ukrainian justice, including simplified procedures, digitalization of the process, a more active role of the judge at the preparatory stage, and the expanded use of mediation. At the same time, it is noted that the implementation of such elements should respect Ukraine’s legal tradition, Constitution, and international obligations. The article also outlines key challenges that hinder the effective functioning of Ukraine’s judicial system. These include excessive procedural workload on courts, complexity of procedures, long case resolution periods, and low public trust. The authors propose a set of recommendations for improving Ukraine’s civil procedural legislation, particularly through the gradual adoption of successful Irish practices. It is concluded that comparative legal analysis with EU legal systems is a crucial tool in shaping Ukraine’s national legal framework, aimed at ensuring effective, accessible, and fair justice.